Evaluation Results From the Healthy Work Collaborative: A Cross-Sectoral Capacity Building Partnership to Address Precarious Employment. Issue 5 (September 2022) - Welter, Christina; Jarpe-Ratner, Elizabeth; Bonney, Tessa; Pinsker, Eve; Fisher, Elizabeth; Deb, Nandini; Yankelev, Anna; Kapadia, Devangna; Love, Marsha; Zanoni, Joseph
Background: The COVID-19 pandemic has illuminated the profound health and safety risks of precariously employed workers, many of whom are disproportionately Latinx and Black. Precarious employment (PE) is a social determinant of health (SDOH) characterized by low wages, hazardous conditions, unstable work schedules, no termination protection, and few benefits. Even before COVID-19, calls for more effective health promotion efforts to address SDOH like PE existed. Purpose: The University of Illinois at Chicago Center for Healthy Work, Healthy Communities Through Healthy Work developed the Healthy Work Collaborative (HWC) as an evidence-informed capacity building policy, systems, and environmental change (PSE) initiative. The HWC aimed to facilitate cross-sectoral partnerships between health and labor sector partners. The labor sector provided technical assistance (TA) to participants to improve their ability to address PE through PSE. Methods: This article reports findings from a mixed-methods evaluation using the Kirkpatrick training model including participants' reactions, learning, behavior, and outcomes. A pre–post survey was administered to participants ( N = 21) and analyzed descriptively; 3-month post HWC interviews were conducted ( N = 13) and thematically analyzed. Conclusion: Findings included positive results at all Kirkpatrick levels. Participants' reported that the HWC curriculum and delivery was valuable and well received; they demonstrated gains toward addressing PE through PSE knowledge and skills and increased or strengthened health/labor partnerships. In addition, HWC influenced participants' application of HWC concepts, and in a few cases, participants' made changes in policies and plans in their organizational settings. The HWC may serve as a model to address other SDOH through cross-sectoral PSE change.